2020
DOI: 10.1590/0074-02760200019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trypanosoma cruzi nucleoside diphosphate kinase 1 in DNA damage responses

Abstract: BACKGROUND NME23/NDPKs are well conserved proteins found in all living organisms. In addition to being nucleoside diphosphate kinases (NDPK), they are multifunctional enzymes involved in different processes such as DNA stability, gene regulation and DNA repair among others. TcNDPK1 is the canonical NDPK isoform present in Trypanosoma cruzi, which has nuclease activity and DNA-binding properties in vitro. OBJECTIVES In the present study we explored the role of TcNDPK1 in DNA damage responses. METHODS TcNDPK1 wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Previous reports have shown that TcNDPK1 has nuclease activity in vitro (Miranda et al, 2008). More recently, Reigada et al (2020) demonstrated the participation of TcNDPK1 in DNA-damage responses. Like most eukaryotic NDPKs, TcNDPK1 forms hexamers (Ulloa et al, 1995;Souza et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports have shown that TcNDPK1 has nuclease activity in vitro (Miranda et al, 2008). More recently, Reigada et al (2020) demonstrated the participation of TcNDPK1 in DNA-damage responses. Like most eukaryotic NDPKs, TcNDPK1 forms hexamers (Ulloa et al, 1995;Souza et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Other NDPKs from pathogens such as parasites are involved in proliferation (Castellanos-Gonzalez et al, 2019). They act as virulence factors (Kolli et al, 2008) and participate in responses to DNA damage (Reigada et al, 2020). Despite many studies, the multiple functions of these enzymes are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a wide variety of unrelated processes from prokaryotes and eukaryotes have been reported in which canonical enzymes play a role. These processes include the following: (a) signal transduction, 27 , 28 (b) virulence and host-pathogen interactions, 29 , 30 , 31 , 32 (c) apoptosis, 33 (d) metastasis, 9 (e) gene regulation 34 and (f) genome integrity, 35 , 36 , 37 among others. 38 , 39 , 40 One intriguing role that deserves special attention, is the case of human NME2, first discovered as Puf, which acts as a transcription factor regulating c-myc expression through binding to a G-quadruplex DNA secondary structure within the promoter region.…”
mentioning
confidence: 99%
“…In this regard, nuclease activity was confirmed for TcNDPK1 17 and, moreover, in a recent study, it was demonstrated that TcNDPK1 is involved in T. cruzi genome integrity maintenance, exerting a protective role against genotoxic agents probably through the up-regulation of enzymes involved in DNA repair. 35 Therefore, the benznidazole resistant phenotype could be associated with this TcNDPK1 function.…”
mentioning
confidence: 99%
“…Estudos com a sua função em tripanosomatídeos são desconhecidos. TcNDPK1 está envolvido na manutenção do DNA genômico e é o único NDPK canônico presente no parasito quando comparado com os demais(REIGADA et al, 2020). A incapacidade dos tripanossomatídeos de sintetizar purinas de novo e sua dependência da via de resgate torna o NDK um alvo atraente para o desenvolvimento de medicamentos para as doenças que esses parasitos causam(MISHRA et al, 2017).…”
unclassified